2021
DOI: 10.1007/s10980-021-01224-8
|View full text |Cite
|
Sign up to set email alerts
|

Changing climate requires shift from refugia to sanctuaries for floodplain forests

Abstract: Context Riparian areas are considered to undergo major alterations under changing climate, making floodplain habitats targets for conservation and landscape planning. Protected areas might provide sanctuaries especially for sessile riparian plant species, but these niches are not always persistent over time. Objectives We investigate if plant species of floodplain forests are provided with suitable habitat within currently protected areas and if these refu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Hydropower infrastructure is known to limit dispersal and migration, which enables climate-related shifts in species distributions, that usually take place toward colder, upstream regions (Nilsson et al, 2005). To our knowledge, there is no research that describes the effect that such infrastructure or channelisation has on the upstream dispersal of riparian plants, but Fink and Scheidegger (2021) show that connectivity along rivers is vital for riparian species to be able to disperse to future suitable habitats.…”
Section: The Climate Crisismentioning
confidence: 99%
“…Hydropower infrastructure is known to limit dispersal and migration, which enables climate-related shifts in species distributions, that usually take place toward colder, upstream regions (Nilsson et al, 2005). To our knowledge, there is no research that describes the effect that such infrastructure or channelisation has on the upstream dispersal of riparian plants, but Fink and Scheidegger (2021) show that connectivity along rivers is vital for riparian species to be able to disperse to future suitable habitats.…”
Section: The Climate Crisismentioning
confidence: 99%
“…Similarly, Kowalska et al (2020); Tockner et al (2002) and Skiadaresis et al (2019) showed that even small management changes can drastically degrade the natural landscape and modify the natural hydrological regimes of alluvial soils. Other authors confirmed that frequently occurring extreme climatic events are associated with increasing global air temperature by 3-4 °C, which affects floodplain forests and wetlands (Ravenga et al 2000;UNEP-WCMC 2001;Kowalska et al 2020;Fink & Scheidegger 2021). They concluded that periodical flooding is a key natural factor facilitating the sustainability and ecological stability of the floodplain forests.…”
mentioning
confidence: 93%
“…Located at the interface between terrestrial and aquatic ecosystems, floodplain forests, mangroves, and floodplain wetlands provide a wide array of crucial ecosystem functions and services (Brown et al, 1997; Hughes, 1988; Hughes & Rood, 2003). Floodplain forests are a source of carbon and nutrients to in‐stream ecosystems (Bunn et al, 2003; Robertson et al, 1999); provide a site for carbon sequestration (Sutfin et al, 2016); provide shade and large woody debris to in‐stream ecosystems (Brown et al, 1997; Mac Nally et al, 2001, 2011); stabilize river banks (Abernethy & Rutherfurd, 1998; Brown et al, 1997); and serve as essential habitat for both terrestrial and aquatic species, such as waterbirds and fish (Brown et al, 1997; Hughes, 1988; Mac Nally et al, 2001), and provide refugia during periods of hydrological and climatic extremes (Fink & Scheidegger, 2021; Sedell et al, 1990).…”
Section: Introductionmentioning
confidence: 99%